Write Here, Right Now An Interactive Introduction to Academic Writing and Research - Tucker, Aaron; Chafe, Paul (Open textbook library., 2018)
Write Here, Right Now: An interactive Introduction to Academic Writing and Research utilizes PressBooks to create and host a writing e-textbook for first year university students that would effectively integrate into the flipped classroom model. The textbook could also be used for non-flipped classroom designs, as the embedded videos, diagrams and linked modules would act as an all-in-one multimedia textbook geared towards multiple learning styles and disciplines. The components of the textbook, including the embedded videos, could be swapped in and out in order to accommodate a professor’s best idea of his/her own course design.